Variables: Plus and Minus
Add x-terms to x-terms and y-terms to y-terms. Do not mix terms.
- x + x =x + x = 2x
- 2x + 2x =2x + 2x = 4x
- 3x + 3x =3x + 3x = 6x
- 4x + 5x =4x + 5x = 9x
- 3x - 2x =3x - 2x = x
- 5x - 3x =5x - 3x = 2x
- 2x - 3x =2x - 3x = -x
- 4x - 7x =4x - 7x = -3x
- x + x + y + y =x + x + y + y =
2x + 2y - 2x + x + 2y + y =2x + x + 2y + y =
3x + 3y - 2x + 3x + 2y + 5y =2x + 3x + 2y + 5y =
5x + 7y - 5x + 3x + 8y + 5y =5x + 3x + 8y + 5y =
8x + 13y - 2x + y + x + 3y =2x + y + x + 3y =
3x + 4y - 2x + y - x + 3y =2x + y - x + 3y =
x + 4y - 5x + 3y - 2x - 2y =5x + 3y - 2x - 2y =
3x + y - (5x + 3y) - 2x - 2y =(5x + 3y) - 2x - 2y =
3x + y - 2x + y - x - 3y =2x + y - x - 3y =
x - 2y - 2x + y - (x - 3y) =2x + y - (x - 3y) =
x + 4y
Notice that in the last pair of cards, the parentheses change the answer because a -1 is distributed into the parentheses, changing the –3y to a +3y.